Impacts of warming and increasing pCO2 on natural phytoplankton communities - Paul, Carolin (2015)
Following the predictions of the IPCC (2014), the water surface temperature in the oceans is proposed to increase by 3-5°C, while at the same time CO2 concentrations in the water are expected to double until the year 2100. A large number of experiments observed effects of warming or rising CO2 concentrations in the water on phytoplankton’s biomass, growth and chemical composition. The combined effects of both climate change factors are to a large extent still unclear. To address the combined effects of warming and rising pCO2 on natural plankton communities, I conducted three mesocosm experiments. Furthermore, I wanted to find out, if seasonal bloom events with their characteristic differences in phytoplankton species composition and growth conditions vary in their responses to climate change. Overall my studies evidence that warming enhances grazing pressure and can alter trophic relations between phytoplankton and their grazers in the pelagic food web. The results showed that warming effects can be translated to the next higher trophic level by switching a summer plankton community from a bottom-up to a mainly top-down controlled system. Further my results point out that warming has the potential to influence phytoplankton’s chemical composition. Observed changes in the content of essential polyunsaturated fatty acids (PUFAs) suggest a possible impact on the food quality for higher trophic levels. Increasing pCO2 concentrations, instead, seem to affect biomass and chemical composition of natural phytoplankton communities only to a lesser extent. Nach Vorhersagen der IPCC (2014), wird die Oberflächentemperatur der Ozeane voraussichtlich um 3-5°C ansteigen, während gleichzeitig damit gerechnet wird, dass sich die CO2 Konzentration im Wasser bis zum Jahre 2100 verdoppelt haben wird. Zahlreiche Experimente stellten den Einfluss von Erwärmung bzw. vom Anstieg des CO2 Gehalts im Wassers auf die Biomasse, das Wachstum und die chemische Zusammensetzung des Phytoplanktons fest. Die Auswirkungen beider Klimafaktoren ...